2015
DOI: 10.1007/s00170-015-7427-1
|View full text |Cite
|
Sign up to set email alerts
|

The effect of graphene oxide (GO) nanoparticles on the processing of epoxy/glass fiber composites using resin infusion

Abstract: In this paper, the effects of graphene oxide (GO) nanoparticles on glass fiber composite processing by incorporating them into epoxy resin were investigated. GO was synthesized from graphite powder and was mixed with epoxy resin. Three different GO contents of 0.05, 0.1, and 0.2 wt% were used. Epoxy/GO samples were tested for rheology and cure kinetics to evaluate the effects of GO content on important resin infusion processing parameters. The results show that adding GO to neat epoxy resin increased the visco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
48
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(49 citation statements)
references
References 51 publications
1
48
0
Order By: Relevance
“…On the other hand, Chen and Yang [6] reported that the modification of natural clays with onium ions could enhance interlayer spacing and thus increasing the glass transition temperature of resulting nanocomposites. In addition, widespread investigations have been made to evaluate the effect of clay inclusions on tensile strength [13][14][15][16], Young's modulus [17,18], tensile creep behavior [19], flexural properties [20][21][22], heat resistance [23,24], barrier performance [25] and flame retardancy [26] of nanocomposites.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, Chen and Yang [6] reported that the modification of natural clays with onium ions could enhance interlayer spacing and thus increasing the glass transition temperature of resulting nanocomposites. In addition, widespread investigations have been made to evaluate the effect of clay inclusions on tensile strength [13][14][15][16], Young's modulus [17,18], tensile creep behavior [19], flexural properties [20][21][22], heat resistance [23,24], barrier performance [25] and flame retardancy [26] of nanocomposites.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the effect of ultrasonication is also clearly demonstrated on clay dispersion in polymer matrices, which has been proven to be highly effective for the dispersion of fine fillers within polymer matrices [21,42]. In the sonication process, when sound waves propagate into the liquid, ultrasound cavities like bubbles take place (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, the test coupons were machined with a diamond coated tooling. The tensile test was measured from un-tabbed 175 3 25 3 2.5 mm 3 specimens, in agreement with the ASTM D 3,039 standard and with a displacement rate of 0.4 mm min 21 ; the initial strain rate was of 0.01 min 21 , using a servohydraulically Instron 8,516 material testing system (Instron corporation, Canton, MA) with a 100 kN load cell and wedge grips.…”
Section: Go-epoxy Carbon Fiber Composite Laminate Preparation and Chamentioning
confidence: 99%
“…Over the last few years, many research works have focused their attention on improving the matrix‐dominated performance of FRC by adding toughening agents such as elastomeric phase and/or nanoparticles such as nanosilica and carbon nanomaterials like carbon black (CB) , carbon nanotubes (CNT) , carbon nanofibers (CNF) and more recently, graphene . Among the manufacturing processes for FRC, the most popular ones are injection technologies, like resin transfer molding (RTM) and resin infusion (RI), due to their short cycles and economic costs.…”
Section: Introductionmentioning
confidence: 99%
“…There are two primary methods used to introduce nanoparticles into composite materials. One method involves dispersing the nanoparticles in the resin [19][20][21][22][23]. However, the high surface area and aspect ratio of the nanoparticles can result in an increase in resin viscosity [17].…”
Section: Introductionmentioning
confidence: 99%